INCREASING FIRST-AID CAPACITY FOR ADOLESCENTS TO SUPPORT A DISASTER-RESILIENT VILLAGE PROGRAM: PENINGKATAN KAPASITAS PERTOLONGAN PERTAMA PADA REMAJA UNTUK MENDUKUNG INISIASI DESA TANGGUH BENCANA - Miftaqul Bilka Subiantoro; Shilvia Ike Nur Salsabila; Tia Rahmawati; Marshanda Mustika; Trijati Puspita Lestari (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: Low biopsy skills risk leading to mishandling fracture cases in the pre-hospital phase. Adolescents were chosen as cadres because they have high mobility and the potential to support community-based preparedness efforts to strengthen Disaster Resilient Villages. Objective: To improve the knowledge and skills of adolescents in conducting fracture bidding as an effort to strengthen emergency preparedness at the village level. Method: This program is carried out in three stages: Preparation, Implementation, and Evaluation and Monitoring. The methods included health education, especially first aid and demonstrations of fracture management, to support the development of alert and resilient adolescents. This activity was conducted on January 26, 2025, for 18 teenagers in Banjarejo Village, Lamongan Regency. Evaluation was carried out using a pre-test and a post-test. Results: Knowledge in the good category increased from 11% to 78%, and 72% of participants were skilled at bidding in accordance with standard operating procedures. Conclusion: This activity contributed to strengthening Disaster Resilient Villages by improving adolescents’ preparedness and emergency mitigation capacity, and the village government is encouraged to develop sustainable community-based emergency training programs.